Analisis Motivasi dan Hambatan Pegawai Puskesmas Melakukan Aktivitas Kebugaran Jasmani dan Pengukurannya (Teori Determinasi Diri) - Henny Arida Purba; Dien Anshari (Journal of Sport Coaching and Physical Education, 2024)
Based on employee fitness measurement data in the 2020 of Sports Health program in Puskesmas Permata Sukarame, employee Vo2max results were obtained with 34% in the sufficient category and 66% in the insufficient category and Vo2max results were found bad category. A fit physical condition has a positive impact on the workforce. This study was designed with a qualitative research approach to fenomenology design. This study found that there was an intrinsic motivation, to measure physical fitness, namely an interest in these activities which had a positive effect on health. Informants got refreshment outside of their daily routine, as well as the need for self-awareness by employees. For extrinsic motivation, namely: appreciation, supervision, responsibility, personal relationships, working conditions, policies and administration. Unfit body condition, weather, lack of time and family become obstacles in measuring physical fitness. It can be concluded that in order to obtain optimal results, interest in the form of hobbies, challenges and responsibilities in the form of self-awareness is needed which comes from intrinsic motivation. For extrinsic motivation, respect, supervision, interpersonal relationships, working conditions and policies and administration are needed. There are also social environmental and physical environmental barriers that prevent employees from measuring physical fitness